Factors of sustainability in mice tourism entrepreneurship: The role of stakeholders and its benefits for SME’s: case study in Yogyakarta - Yuniati, Nining; Prakosa, Aditha Agung; Susilo, Susilo (Universitas Merdeka Malang, 2025)
One important activity for tourism promotion is organizing various MICE (Meeting Incentive Conference Exhibition) events on both local and international scales. MICE is a business primarily supported by SMEs, both as organizers and suppliers/vendors. However, MICE business owners often don't understand how to keep their businesses sustainable, and suppliers often just hope their businesses continue without understanding how. This research aims to identify factors that can support the business continuity of MICE industry players. The study was conducted using the grounded theory model, starting with in-depth interviews with event organizers and suppliers in Yogyakarta to identify factors that would be used to develop a theory, with the assistance of coding in NVIVO software. These factors, which were transformed into a theory, were then directly tested on business actors (80 respondents) using multiple regression analysis. Based on the results of the regression test, it was found that the 8 keywords generated from NVIVO data processing do indeed have a significant influence on supporting the sustainability of the MICE business, both partially and simultaneously. The eight keywords are Commitment & Contract, Innovation & Novelty of Event; Mutual Partnership; Payment; Portfolio & Experience; Product Quality; Profit; Zero Complaint.